Rénovation méthodologique dans l’historiographie littéraire en belgique francophone au xxie siècle
Our goal in this study is to write an overview as detailed as possible about the methodological changes in the methodology experienced by literary historiography in Francophone Belgium from the very beginning of the seventies (the beginning of the so called “dialectical” phase). During this decade, in direct connection with several identity reframings and with the social and political evolution of the country (the federalization process), both qualitative and quantitative significant changes occurred. From that point and on, critics such as Klinkenberg, Quaghebeur, Lambert and many of their disciples stopped to examine literature produced in Francophone Belgium in terms of purely French criteria; influenced in particular by the sociological and institutional models of Bourdieu and Dubois, they proposed different concepts and methods that allow to study new aspects and features of the francophone Belgian literature.